Marketing Research - Nguyen, Thi Hong Hanh (Khoa Quốc tế, ĐHQGHN, 2020)
This course helps students understand and grasp the knowledge necessary to design and implement a marketing research project, including: identifying and specifying the research subject, designing research projects, identifying data resources, research methods (qualitative and quantitative), techniques to gather information (design of interview guidelines, multiple choice questionnaires, measuring tools, sampling methods, etc.), data analysis (basic statistical measurement and analysis of quantitative data), reporting the results of research for marketing decision making.